Pharmacokinetic modelling to predict risk of ototoxicity with intravenous tobramycin treatment in cystic fibrosis. (11th August 2021) - Dong, Min; Rodriguez, Anna V; Blankenship, Chelsea A; McPhail, Gary; Vinks, Alexander A; Hunter, Lisa L
Abstract: Introduction: Further optimization of therapeutic drug monitoring (TDM) for aminoglycosides (AGs) is urgently needed, especially in special populations such as those with cystic fibrosis (CF), >50% of whom develop ototoxicity if treated with multiple courses of IV AGs. This study aimed to empirically test a pharmacokinetic (PK) model using Bayesian estimation of drug exposure in the deeper body tissues to determine feasibility for prediction of ototoxicity. Materials and methods: IV doses ( n  = 3645) of tobramycin and vancomycin were documented with precise timing from 38 patients with CF (aged 8–21 years), including total doses given and total exposure (cumulative AUC). Concentration results were obtained at 3 and 10 h for the central (C1) compartment. These variables were used in Bayesian estimation to predict trough levels in the secondary tissue compartments (C2 trough) and maximum concentrations (C2max ). The C1 and C2 measures were then correlated with hearing levels in the extended high-frequency range. Results: Patients with more severe hearing loss were older and had a higher number of tobramycin C2max concentrations >2 mg/L than patients with normal or lesser degrees of hearing loss. These two factors together significantly predicted average high-frequency hearing level (r = 0.618, P   <  0.001). Traditional metrics such as C1 trough concentrations were not predictive. The relative risk for hearing loss was 5.8 times greater with six or more tobramycin courses that exceeded C2max concentrations of 3 mg/L or higher, with sensitivity of 83% and specificity of 86%. Conclusions: Advanced PK model-informed analysis predicted ototoxicity risk in patients with CF treated with tobramycin and demonstrated high test prediction.